Apportionment of PM2.5 adjacent to the I-710 Harbor Freeway in Long Beach, CA. (3rd March 2020) - Eatough, Delbert J.; Cropper, Paul; Keeton, William; Burrell, Emily; Hansen, Jaron C.; Farber, Rob; Zack, John; Cary, Robert A.; Hopke, Philip K.
ABSTRACT: During August and September 2012, a study was conducted to determine the sources of PM2.5 adjacent to the I-710 Long Beach Freeway. The site is directly affected by the emissions from heavy diesel traffic flowing from major container ports about 10 km south of the sampling site. Hourly average data were obtained for particulate species including PM2.5, black carbon and UV absorbing carbon, EC, fine particulate nonvolatile and semi-volatile organic material (NVOM and SVOM), sulfate, nitrate, chloride, ammonium ion, and Na ion, and for related factors including O3, CO, NOX, SO2, and total traffic flow on the I-710. A total of 520 hourly averaged data sets with 15 measured variables were analyzed by EPA-PMF v5.0. The data were best described by a 10-factor solution. Based on the composition and diurnal patterns of the factors, they were assigned to three diesel-related factors (two of which appeared to represent traffic from the ports and one general freeway diesel factor), a light-duty, spark-ignition vehicle-related factor, three secondary factors (one of which was associated with O3 formation processes), and three factors dominated by sulfate, SO2, and chloride, respectively. The diurnal patterns for these last three factors are strongly correlated. Meteorological and refinery upset data indicate that they are associated with emissions from a nearby refinery. The results of the PMF analysis were combined with nephelometer light scattering, corrected for coarse particle scattering and estimated aerosol water content in a multilinear regression analysis to identify visibility degradation sources. Major contributors were the aerosol water content, and the secondary PMF factors associated with either Nitrate and NVOM or NVOM and SVOM. The use of hourly average data made possible the identification of factors associated with gasoline vehicle emissions and both port and non-port diesel emissions. Implications : Hourly averaged data were obtained for PM2.5, its components and factors related to primary emissions and the formation of secondary material at a near freeway sampling location adjacent to the I-710 freeway just south of the Long Beach Boulevard entrance and 10 km north of the Ports of Long Beach and Los Angeles. The major objective of the study was to determine the impact of traffic from the ports at the monitoring site. This manuscript reports on the PMF analysis of the data set. Factors related to both diesel traffic originating from the ports and diesel traffic from non-port origins were identified. The diesel traffic originating from the ports was responsible for 9% of the total traffic and 95% of the BC measured at the sampling site. The non-port diesel traffic was responsible for 15% of the total traffic and 5% of the BC. While the Port 1 diesel traffic coming from the ports contributed a large fraction of the BC, this source contributed only 2% of the CO and 5% of the NOX at the sampling site. The impact of these traffic sources on light scattering was also small. Analysis of sources of sulfate and SO2 at the sampling site indicated that these species did not come from port activities of ships at or approaching the port, but rather from upset flare events at a nearby oil refinery.